Traditional Handicraft Village in Thanh Hoa Today - Thi Buoi, MSc. Le (International Journal of Humanities and Education Development (IJHED), 2022)
Thanh Hoa is a land with a rich history and culture, with many long-standing traditional handicraft villages, which have been lost over time, now gradually been restored and promoted their values ​​in modern life. In the spirit of Decree No. 52 dated April 12, 2018, of the Government on the development of rural industries, Thanh Hoa province has issued many mechanisms and policies to encourage the development of traditional handicrafts. The article focuses on clarifying the system of traditional craft villages in Xu Thanh (The Land of Thanh), the size, characteristics and guidelines, and policies of Thanh Hoa province to maintain and develop handicraft villages to serve the economy - social sustainability.